Protective Effect of Combination Black Seed Oil (Nigella sativa) and Honey on the Duodenum of Rats Exposed to Cisplatin - Wasilah, Khusnul; Ilmiawan, Muhammad In’am; Handini, Mitra (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2023)
Background: Cisplatin (CP) is an anticancer agent with various side effects, including duodenal mucosal damage. It is well known that black seed oil (BSO) and honey (H) are rich in antioxidants and have a mucosal protective effect. Purposes: To determine the protective effect of the BSO and H combination on the histopathology of duodenal rats given CP exposure. Methods: Randomized post-test-only control group design was used in this study. A total of 30 rats were divided into ten groups, namely the control group (K), treatment groups (P1-P8), and cisplatin group (C). The treatment groups were given BSO and H orally for 21 days, and CP was given intraperitoneally on day 18 to the treatment and cisplatin groups. On day 22, the duodenal tissue was taken for preparation and histopathological assessment. Data analysis using IBM SPSS v.24 and Compusyn program. Result: There were significant differences in the duodenal mucosa damage scores of the P1-P8 group compared to the C group (p0.05). The combination index of P7 exerted a synergism effect (CI 1). Conclusion: The combination of BSO and H exerted a protective effect on the histopathological of rats’ duodenal tissue induced with CP, and the combination of BSO 2 mL/KgBW and H 3.7 mL/KgBW exerted a synergism effect.